Ornithofauna of the high-mountain open terrains on the Šar Mountain (faunistical and ecological analysis) - Micevski, Branko (Macedonian Journal of Ecology and Environment, 1994)
In the period from 1984 to 1994, surveying of the bleeding avifauna of the high mountain open terrains (high mountain grasslands and rocky terrains) of the Šar Mountains were carried out. The survey region extends from the River Pena in the north to the River Piročka in the south. For this terrain, without counting the species which were registered only in the tourist place Popova Sapka, adjacent small spruce woodlands surrounded by the surveyed terrain, or birds which obviously belong to the lower-forest communities, 34 bird species have been studied (ecologically and biogeographicaly) and the results are presented in this paper.